Attentional demands on motor-respiratory coordination - Hessler, E. E.; Amazeen, P. G. (Research Quarterly for Exercise and Sport, 2009)
Athletic performance requires the pacing of breathing with exercise, known as motor-respiratory coordination (MRC). In this study, we added cognitive and physical constraints while participants intentionally controlled their breathing locations during rhythmic arm movement. This is the first study to examine a cognitive constraint on MRC. Cognitive constraints included either instruction (Experiments 1 and 2) or signal detection (Experiment 1). Physical constraints were nonoptimal movement frequencies (Experiment 2). Instruction shifted breathing locations and both shifted and increased variability in the number of movements produced per breath (frequency ratio). Signal detection had no effect on MRC. Fast movement frequency resulted in higher, more variable frequency ratios. Cognitive and physical constraints can generate unnatural and variable breathing during athletic performance.